Environmental history of early India : a reader - Kapur, Nandini Sinha (ed.) (New Delhi, 2011)
The last decade has seen a spurt of writings on environmental history. However, a history of early India has rarely been constructed from this perspective. One of the first anthologies on the subject, this reader, presents a comprehensive survey of environmental history in ancient and early medieval India. It examines significant aspects of early Indian society and state, and their relationship with the natural environment. Presenting a multidimensional analysis, this volume discusses various aspects of the history of the environment in early and early medieval India like: deforestation, agricultural expansion, settlement patterns, and royal sanctions and charters related to forests; development of irrigation and water resources; significance of marginal communities, and the impact of Puranic religion on topography; pastoralism and agrarian economy; botany and plant sciences in ancient India.
Keywords: Environment-History-Early India